2017
DOI: 10.14334/jitv.v21i3.1574
|View full text |Cite
|
Sign up to set email alerts
|

Response of sheep fed on corn cob silage or elephant grass basal diet with or without Calliandra leaf meal supplementation

Abstract: ABSTRAKYulistiani D. 2016. Respon domba yang diberi pakan dasar silase tongkol jagung atau rumput gajah dengan atau tanpa suplementasi Kaliandra. JITV 21(3): 165-173. DOI: http://dx.doi.org/10. 14334/jitv.v21i3.1574 Terbatasnya ketersediaan hijauan pakan sepanjang tahun dapat diatasi melalui penggunaan hasil samping pertanian. Tongkol jagung, hasil samping produksi jagung potensial untuk digunakan sebagai sumber serat pengganti rumput. Tujuan dari penelitian ini untuk membandingkan pengaruh dua jenis pakan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, its acceptability is less due to its palatability concern. Preferably, intake and digestibility constraints of feeding rice straw can be improved by the application of pre-treatment methods (physical, chemical and biological) or supplementation with other feedstuff components in the simplest way possible (Yulistiani et al, 2003;Sarnklong et al, 2010;Oladosu et al, 2016;Patra and Aschenbach, 2018). Rice straw under the pre-treatment process has a positive effect on the conversion of its chemical compositions that each procedure only differs according to preferred manipulation schemes (Maurya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its acceptability is less due to its palatability concern. Preferably, intake and digestibility constraints of feeding rice straw can be improved by the application of pre-treatment methods (physical, chemical and biological) or supplementation with other feedstuff components in the simplest way possible (Yulistiani et al, 2003;Sarnklong et al, 2010;Oladosu et al, 2016;Patra and Aschenbach, 2018). Rice straw under the pre-treatment process has a positive effect on the conversion of its chemical compositions that each procedure only differs according to preferred manipulation schemes (Maurya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rice straw under the pre-treatment process has a positive effect on the conversion of its chemical compositions that each procedure only differs according to preferred manipulation schemes (Maurya et al, 2015). Relatively, pre-treatment methods such as the use of urea or supplementation with high-quality feed like legumes can improve the low nutritional value and palatability of rice straw (Yulistiani et al, 2003;Ma et al, 2020). Moreover, Bata et al (2020) further revealed that urea-treated rice straw ensiled with cassava pulp and supplemented with concentrate can improve production and reproduction performance in the case of heifer buffaloes.…”
Section: Introductionmentioning
confidence: 99%